PENGEMBANGAN INSTRUMEN UJI KOMPETENSI GURU BAGI CALON GURU MATEMATIKA SMA - Sablis Salam Salam; Yenita Roza Roza; Zuhri D ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The teacher competence test is a test which is conducted to observe the competence mastery of a teacher. That mastery will be used as the basic consideration on training program and developing the professional teacher. The score of competence test of high school mathematics teacher in Riau province was 41,34, meanwhile the score of expected standard is 70. One of the factors which caused the low score was the teacher having lack of training about the problem of teacher competency test. This research is development research which aims to develop the instrument of competence test of high school mathematics teacher. The development model of this research is FOUR-D models, which consist of four stages; Define, Design, Develop, Dissemmination. The subject were the students at class Mathematics Education 2012 in Riau University on the sixth semester. The technique of data analy